Implementation of Good Government Governance through E-Government - Suardini, Deni; Mariana, Dede; Rahmatunnisa, Mudiyati; Setiabudi Sumadinata, Widya (International Journal of Engineering and Technology, 2018)
The article explain about the implementation of e-government management in Tasikmalaya city, West Java. Using a qualitative approach, the researcher is an instrument obliged to collect, process, analyze, interpret and verify the data and information. The observation and participatory research done by observing the processes of implementation of policy implementation of e-government in Tasikmalaya, which concerns such aspects as idealized policy, implementing organization, target groups, and environmental factors. Data and information through observation and in-depth interviews to informants are the key in collecting the data. The validity and reliability of data and information are performed by triangulation, clarification and description explained and verified by theories of public policy and science administration to formulate answers from the research questions. The result of this research shows that the implementation of e-government policy in Tasikmalaya city has not shown towards the understanding of the policies that favor e-government in the city of Tasikmalaya. The ideal policy on the implementation of e-government were not yet properly implemented by the fact that in implementing organization in the department of communication of Tasikmalaya city were not optimally effective in coaching, services and protection as well as socialization and the process and preparation of program planning. In this case the aspirations of the people are less involved in the formulation of the policy of e-government implementation resulted in the implementation; it did only accept without commenting and understanding the implementation of the e-government.Â Â